Indonesia Islamic Bank Development: An Interpretive Structural Modeling (ISM) - Rusydiana, Aam Slamet; Laila, Nisful; Ali, Mohammad Mahbubi (Review on Islamic Accounting, 2023)
This research is aim to identify the priority factors that being barrier to develop Islamic bank in Indonesia using Interpretive Structural Modeling (ISM) method. Here is also offered some solutions for the problems identified. ISM is an advanced planning methodology used to identify, analyze and summarize various relationship among factors that define a problem, model or issue. The development of Islamic bank in Indonesia with ISM framework is divided into three criteria: (1) Strategy or foundation required within the framework of developing Islamic banks, and (2) Stakeholders or actors involved in the development of Islamic banks in Indonesia. Result show that the core strategies or foundations that’s needed in framework of Islamic banking development in Indonesia are: The improvement of public literation and preference, Strengthening and align ruling and supervision, Strengthening policy synergy between the stakeholders and Improvement quality and quantity of human resources, information system & technology and other infrastructures.